2010
DOI: 10.1002/hipo.20698
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of electrocorticographic activity during pharmacological preconditioning and seizure induction by intrahippocampal domoic acid

Abstract: Previously we have shown that low-dose domoic acid (DA) preconditioning produces tolerance to the behavioral effects of high-dose DA. In this study, we used electrocorticography (ECoG) to monitor subtle CNS changes during and after preconditioning. Young adult male Sprague-Dawley rats were implanted with a left cortical electrode, and acute recordings were obtained during preconditioning by contralateral intrahippocampal administration of either low-dose DA (15 pmoles) or saline, followed by a high-dose DA (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Immediately after drug administration, the animals were returned to the observation chamber and their behaviors were observed for 2 hours in a cycle of 1 minute on and 4 minutes off, with all behavioral responses during each observation period coded and logged electronically, as described previously. 8,11,13 Behaviors were rated using a modified version of the seizure scale: level 0, normal resting or exploratory behaviors; level 1, discomfort behaviors; level 2, stereotypical behaviors confined to the head and neck region; level 3, moderate seizure behaviors associated with stereotypical movements of the limbs or trunk; and level 4, severe generalized seizure behaviors, with level 4 leading to level 5, clonic-tonic convulsions. Animals experiencing more than two periods of prolonged clonictonic convulsions were immediately sacrificed in compliance with ethical requirements and all subsequent observation periods were logged as level 5.…”
Section: Behavioral Analysis After Dom Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after drug administration, the animals were returned to the observation chamber and their behaviors were observed for 2 hours in a cycle of 1 minute on and 4 minutes off, with all behavioral responses during each observation period coded and logged electronically, as described previously. 8,11,13 Behaviors were rated using a modified version of the seizure scale: level 0, normal resting or exploratory behaviors; level 1, discomfort behaviors; level 2, stereotypical behaviors confined to the head and neck region; level 3, moderate seizure behaviors associated with stereotypical movements of the limbs or trunk; and level 4, severe generalized seizure behaviors, with level 4 leading to level 5, clonic-tonic convulsions. Animals experiencing more than two periods of prolonged clonictonic convulsions were immediately sacrificed in compliance with ethical requirements and all subsequent observation periods were logged as level 5.…”
Section: Behavioral Analysis After Dom Administrationmentioning
confidence: 99%
“…1 As a consequence of heightened interest in the mechanism of DOM toxicity, a number of experimental studies have investigated the consequences of DOM exposure on behavioral and neurological responses in laboratory animals. 4,[7][8][9][10][11][12][13] Within neuronal tissue, DOM has been shown to activate ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and kainic acid (KA) receptors and results in the release of glutamate. 14 Overstimulation of ionotropic glutamate receptors (iGluR), namely N-methyl-D-aspartate (NMDA) receptors, provokes pathophysiological increases in intracellular Ca 2ϩ and consequently leads to the activation of several overlapping Ca 2ϩ -dependent processes, such as the generation of mitochondrial reactive oxygen species and loss of cellular viability.…”
mentioning
confidence: 99%
“…11 Excitotoxic seizure induction with KA in rat models produces escalating levels of behavioural responses which include head tremors, wet dog shakes (WDS) and eventually clonic-tonic convulsions. 12,13 Previous studies by our group demonstrated that neither KA nor domoic acid produce direct toxic effects on rat cardiomyocyte or isolated heart preparations. 14 Furthermore, we have shown that domoic acid-induced SE produces identical patterns of structural cardiomyopathy, irrespective of whether the excitotoxin is delivered through central or systemic routes.…”
Section: Introductionmentioning
confidence: 99%
“…D omoic acid (DA), a naturally occurring marine neurotoxin produced by members of the diatom genus Pseudonitzschia, has been reported to be a structural relative to kainic acid (KA) and can induce neuronal excitotoxicity via activation of aminopropionic acid and KA receptors (1)(2)(3)(4). Several lines of evidence show that activation of KA receptors impairs mitochondrial function, provokes the release of inflammatory factors, and increases the generation of reactive oxygen species (ROS), which disrupt neural signaling pathways and cause structural cellular damage, ultimately leading to cognitive deficits and brain damage (2,(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%